The development of stochastic SIR-SI Age-Structured model for leptospirosis mapping in Malaysia - Aznida Che Awang (Tanjong Malim, 2018)
The development of stochastic SIR-SI Age-Structured model for leptospirosis mapping in Malaysia by Aznida Che Awang